Correlations of attended and unattended blood pressure with sympathetic nervous system activity in essential hypertension. (25th November 2020) - Manta, E; Kouremeti, M; Kakouri, N; Kasiakogias, A; Konstantinidis, D; Papakonstantinou, P; Kalos, T; Liatakis, I; Tousoulis, D; Tsioufis, C
Abstract: Background/Introduction: Measurement of unattended blood pressure (BP) may provide additional information over conventionally attended BP. Moreover, hypertension is related to sympathetic drive while there are scarce data on the diverse links of attended and unattended BP with muscle sympathetic nerve activity (MSNA) in hypertensive patients. Purpose: The aim of this study was to appraise the relation of BP levels in the attended and unattended setting with MSNA in patients with essential hypertension. Methods: We studied 117 patients with essential hypertension (age: 58±11 years, 60 males, office BP: 142/85±17/10 mmHg, 24-hour BP: 133/80±11/9 mmHg). In all participants sympathetic drive was assessed by MSNA estimations based on established methodology (microneurography). Both unattended BP (patient alone in the room, an oscillometric device programmed to perform 3 BP measurements, at 1-minute intervals, after 5 minutes) and attended BP were measured with the same device, on the same day of MSNA recording, in random order. Patients were divided into the combined attended and unattended hypertensive group when BP≥140/90 mmHg in both attended and unattended BP estimations and to the attended hypertensive group when only attended BP≥140/90 mmHg. Results: Patients with combined attended and unattended hypertension (n=70) compared to those with attended hypertension (n=47) did not differ regarding 24-h ambulatory BP levels, glucose levels, renal function and left ventricular mass index (p=NS for all). Moreover, patients with combined attended and unattended hypertension compared to those with attended hypertension were characterized by greater levels of MSNA (43.7±9.9 vs 37.7±9.7 bursts per minute, p=0.032). In all participants, sympathetic nerve traffic as assessed by resting MSNA was related to attended systolic BP (r=0.270, p=0.003), attended diastolic BP (r=0.344, p=0.001), unattended systolic BP (r=0.263, p=0.004) and unattended diastolic BP (r=0.274, p=0.003). Conclusions: The phenotype of combined attended and unattended hypertension compared to attended hypertension is accompanied by higher sympathetic nervous system activation. Moreover, the close association of MSNA with attended and unattended BP levels in essential hypertension, further supports the key role of sympathetic drive in modulating BP. Funding Acknowledgement: Type of funding source: None